Global parental leave in surgical careers: differences according to gender, geographical regions and surgical career stages. Issue 11 (1st September 2021) - Au, S; Bellato, V; Carvas, J M; Córdoba, C D; Daudu, D; Dziakova, J; Eltarhoni, K; El Feituri, N; Fung, A C H; Fysaraki, C; Gallo, G; Gultekin, F Ayca; et al.
Abstract: Background: There is a lack of information regarding the provision of parental leave for surgical careers. This survey study aims to evaluate the experience of maternity/paternity leave and views on work–life balance globally. Methods: A 55-item online survey in 24 languages was distributed via social media as per CHERRIES guideline from February to March 2020. It explored parental leave entitlements, attitude towards leave taking, financial impact, time spent with children and compatibility of parenthood with surgical career. Results: Of the 1393 (male : female, 514 : 829) respondents from 65 countries, there were 479 medical students, 349 surgical trainees and 513 consultants. Consultants had less than the recommended duration of maternity leave (43.8 versus 29.1 per cent), no paid maternity (8.3 versus 3.2 per cent) or paternity leave (19.3 versus 11.0 per cent) compared with trainees. Females were less likely to have children than males (36.8 versus 45.6 per cent, P  = 0.010) and were more often told surgery is incompatible with parenthood (80.2 versus 59.5 per cent, P  < 0.001). Males spent less than 20 per cent of their salary on childcare and fewer than 30 hours/week with their children. More than half (59.2 per cent) of medical students did not believe a surgical career allowed work–life balance. Conclusion: Surgeons across the globe had inadequate parental leave. Significant gender disparity was seen in multiple aspects. Abstract : A survey exploring parental leave received responses from both men and women from 65 countries. The study demonstrates that a considerable proportion of surgeons had inadequate maternity/paternity leave. Gender inequity was a more significant finding than geographical and career stage differences in the experience of maternity/paternity leave and parenthood.